2016
DOI: 10.1371/journal.pone.0154824
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Virus Like Particle Forming Baculoviral DNA Vaccine against Pandemic Influenza H1N1

Abstract: An outbreak of influenza H1N1 in 2009, representing the first influenza pandemic of the 21st century, was transmitted to over a million individuals and claimed 18,449 lives. The current status in many countries is to prepare influenza vaccine using cell-based or egg-based killed vaccine. However, traditional influenza vaccine platforms have several limitations. To overcome these limitations, many researchers have tried various approaches to develop alternative production platforms. One of the alternative appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The titers of neutralizing antibodies and IFN-c secretion elicited by Ac mPERV-C5/C6 expressing GP5 and M proteins were higher than those by Ac mPERV-C5 expressing GP5 only. Our results are consistent with previous reports 21 showing that DNA vaccines encoding VLP forming antigen generated stronger immunogenicity than those encoding a single major antigen gene.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The titers of neutralizing antibodies and IFN-c secretion elicited by Ac mPERV-C5/C6 expressing GP5 and M proteins were higher than those by Ac mPERV-C5 expressing GP5 only. Our results are consistent with previous reports 21 showing that DNA vaccines encoding VLP forming antigen generated stronger immunogenicity than those encoding a single major antigen gene.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, we reported the immunization efficacy of influenza DNA vaccines based on a HERV-coated baculoviral DNA vaccine system for human use. 5,21 In this study, we successfully constructed a PERVenveloped baculovirus delivery system for porcine use. Compare to full length of PERV env, signal sequence and transmembrane modified PERV env showed more efficient delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The virus-like particle (VLP) vaccine has been shown to induce long-term protection of mice from influenza virus infection [50, 51]. However, construction and production of these VLP vaccines at an industry scale are cumbersome [52]. Unlike VLP vaccines, yeast vaccines can be produced at large-scale and in a very cost-effective way.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, DNA vaccines can induce strong and long‐lasting humoral and cell‐dependent immune responses (Thermet, Rollier, Zoulim, Trepo, & Cova, ). In a vaccination study of mice, Gwon et al () reported that, compared with BALB/c mice immunized with the killed vaccine, mice immunized with virus‐like‐particle (VLP)‐forming DNA vaccine can produce a strong neutralizing antibody and a high level of interferon‐γ with an intrasubgroup H1 strain.…”
Section: Discussionmentioning
confidence: 99%